Analyzing Student Needs for Developing Effective Instructional Media in Correspondence Practice - Sutirman Sutirman; Yuliansah Yuliansah (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the era of Industrial Revolution 4.0, vocational students must possess strong correspondence skills to meet modern workplace requirements. However, instructional media used in Vocational High School (VHS) Office Management and Business Services (OMBS) programs in the Special Region of Yogyakarta are not yet aligned with students' learning characteristics. This study aimed to identify the instructional media needs of 430 VHS OMBS students to support the development of their correspondence competencies. A quantitative descriptive approach was used, with data collected through a structured questionnaire. The findings revealed three key points: (1) students face significant difficulties in sentence construction and understanding correspondence materials; (2) traditional tools such as Microsoft Word and handwritten exercises remain dominant in classrooms; and (3) students exhibit a strong preference for web-based instructional media. Notably, students in public VHS institutions reported greater access to web-based platforms, while those in private schools highlighted their usability and efficiency. These results indicate a misalignment between current instructional methods and student preferences, particularly in leveraging digital tools for communication skills development. The study highlights the urgent need for vocational education stakeholders to adopt more adaptive, web-based instructional media. Doing so can enhance students’ readiness for professional communication in increasingly digital work environments.